Carbon Disclosure, Board Climate Governance and Financial Performance of Listed Manufacturing Firms in Nigeria - Akhanolu, Isibor Areghan; Benjamin, Ehikioya; Adebayo, Mercy; Bolanle, Awogbenja Bukola; Bunmi-Alo, Adedoyin (International Journal of Energy Economics and Policy, 2023)
This study examined the challenges of carbon disclosure and its impact on the performance of quoted manufacturing firms in Nigeria. Using equity return (ROE) as the dependent variable and carbon performance (disclosure), board response, board climate incentives, and board environmental committee as the independent variables, the study used panel data analysis to analyze the secondary data gathered from 2014 till 2020. The Hausman test suggested the usage of the fixed effect regression. Findings from the regression result showed that all the independent variables of carbon performance (disclosure), board response, board climate incentives, and board environmental committee positively and significantly impact ROE. The study therefore recommended amongst others that firms should always disclose their carbon disclosure data on their annual data so as to assist both the board and the regulatory authorities in managing carbon emission.